Usefulness of PET/CT for early detection of internal malignancies in patients with Muir–Torre syndrome: report of two cases - Yui Ishiguro; Shigenori Homma; Tadashi Yoshida; Yosuke Ohno; Nobuki Ichikawa; Hideki Kawamura; Hiroo Hata; Satoru Kase; Susumu Ishida; Hiromi Okada-Kanno; Kanako C. Hatanaka; Akinobu Taketomi (Surgical Case Reports, 2017)
Abstract Background Muir–Torre syndrome (MTS) is a rare autosomal dominant genodermatosis caused by mutations in mismatch repair genes. It is characterized by the presence of at least one sebaceous skin tumor associated with internal malignancies. Whether positron emission tomography/computed tomography (PET/CT) is useful for the detection of malignancies in patients with MTS has not been determined. We herein report two cases in which PET/CT was useful for the diagnosis and follow-up of internal malignancies in patients with MTS. Case presentation In case 1, a 57-year-old woman underwent excision of a sebaceous carcinoma on the left upper eyelid. She underwent follow-up PET/CT once yearly thereafter. Forty-two months after the eyelid surgery, PET/CT showed intense tracer uptake in the right lower abdomen. An ascending colon tumor was identified, and examination of a biopsy specimen showed adenocarcinoma. In case 2, a 77-year-old man presented for evaluation of three continuous papules with telangiectasia on his right cheek. Examination of a skin biopsy specimen of the cheek papule revealed a sebaceous carcinoma. He underwent PET/CT to detect other malignancies. PET/CT showed intense tracer uptake in the sigmoid colon. A sigmoid colon tumor was identified, and examination of a biopsy specimen showed adenocarcinoma. Both patients underwent resection of their tumors, and both were still free of recurrence of the sebaceous and colon carcinomas at the time of this writing. Conclusion PET/CT is a reliable imaging modality for the detection of internal malignancies and is useful for the diagnosis and follow-up of MTS.